I don't understand.
Didn't you post the formula with a +/- ?
so in your equation x^2 - 25 = 0
a = 1
b = 0
c = -25
so x = (0 ±√(0-4(1)(-25))/2
= ±√100 / 2
of course the easier way would be to write the equation as
x^2 = 25 , then
x = ±√25 = ±5
Yes I did post it with a +/- representing plus or minus the number.
How were you about to show the +- with the minus sign uder the the plus sign?
I looked at the answer you provided I think I can see my error. I was taking 0 for C not the 25. I remember now that C has to be a number without a variable next to it.